Single nucleotide polymorphism array analysis in copy number variant detection: assessment of its feasibility in the diagnostic setting - Ruppelt, Theresa (Division of Human Genetics, 2017)
Intellectual disability/developmental delay (ID/DD) is a significant problem in child health affecting 2 to 3% of the population worldwide. While the underlying aetiology of ID/DD in a large proportion (about 50%) of these patients is unknown, 15 to 20% of the internationally reported cases detected using microarray technologies are due to copy number variants (CNVs), whereas only 3 to 5% of ID/DD can be identified with conventional cytogenetics. The Affymetrix® Cytoscan™ High Density (HD) Array (Affymetrix, Santa Clara, CA) containing over 2.4 million markers for copy number (CN) was used to detect genome-wide high resolution CN and single nucleotide polymorphisms (SNPs) in a cohort of 27 carefully selected patient samples. The patient selection was done based on relevant phenotypes, which included dysmorphism, ID/DD, suspected syndromes, and family history. Data analysis was performed using the Affymetrix Chromosome Analysis Suite (ChAS) (Affymetrix, Santa Clara, CA, USA software). Seven of the patients demonstrated pathogenic CNVs. Diagnoses included Kleefstra syndrome, Mowat-Wilson syndrome, Wolf-Hirschhorn syndrome, tetrasomy 9p, and a susceptibility locus for neurodevelopmental disorders due to a deletion of chromosome 1q21.1. This indicated a 26% detection rate in this cohort. In addition, three variants of unknown significance (VOUS) were detected. The aim of this study was to determine the potential relevance and applicability of microarray technologies for the detection of CNVs in the Western Cape ID/DD population of South Africa (SA) and in so doing, to introduce and develop molecular cytogenetics skills in the routine diagnostic cytogenetic environment. The results obtained in this study confirmed the significant improvement in the detection rate of CNVs in patients with ID/DD and thus the diagnostic utility of this technology for the detection of CNVs in ID/DD patients was confirmed.